Mineral fiber board complex and method of preparing same
Patent Information
- Application Number
- KR1020210075883
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-06-18
- Filing Date
- 2021-06-11
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2041-06-11
Smart Images

Figure 112021067475017-PAT00002_ABST
Abstract
Description
Technology Field
[0001] The present application relates to a mineral-based fiber board composite and a method for manufacturing the same, and more specifically, to a mineral-based fiber board composite and a method for manufacturing the same that can minimize the defect rate of a mineral-based fiber board with a low-pressure melamine sheet attached and improve the adhesion of the low-pressure melamine sheet. Background Technology
[0003] Mineral fiber boards are a general term for building materials that utilize fibers made by melting minerals, such as basalt or granite, at high temperatures.
[0004] In the past, mineral fiber boards were used by using mineral fibers as aggregates, mixing them with resin (especially phenolic resin) to secure strength and bonding power, and processing them into a board shape by heat compression.
[0005] In particular, it has been used for insulation and exterior materials, but recently, due to its low tVOC non-combustibility, its potential for use as an interior material is increasing.
[0006] However, due to the characteristics of aggregates composed of mineral fibers, they lack hardness and generate dust during processing, causing many problems.
[0007] Therefore, it is necessary to apply surface materials or perform surface treatment. Certain materials have been suggested as candidates for this purpose.
[0008] In addition, due to the high strength, low shrinkage rate, and low thermal expansion rate of the material itself, problems such as surface defects and poor adhesion are likely to occur when applying surface materials.
[0009] Therefore, it is time to conduct research on methods to resolve these issues and simultaneously improve surface defects and adhesion failures when using mineral fiber boards by selecting appropriate surface materials and utilizing suitable manufacturing processes. The problem to be solved
[0011] According to one embodiment of the present application, the defect rate of a mineral-based fiber board with a low-pressure melamine sheet attached is minimized and the adhesion of the low-pressure melamine sheet is improved, and a method for manufacturing the same is provided. means of solving the problem
[0013] One aspect of the present application provides a mineral-based fiber board composite.
[0014] As an example, the mineral fiber board composite comprises a surface material; a mineral fiber core material; and a surface material in sequence, wherein the weight of melamine per unit area included in the composite is 80 to 110 g / m² and the adhesion strength between the mineral fiber core material and the surface material may be 0.1 to 100 kgf / cm² as a result of the ASTM D4541 adhesion test.
[0015] As an example, the composite may have a hardness of 4B to 3H in the ISO 15184 pencil hardness test.
[0017] As an example, the surface material may include a low pressure melamine sheet.
[0018] As an example, the surface material may additionally include any one of ASA (acrylonitrile styrene acrylate), PP (polypropylene), PET (poly(ethylene terephthalate)), and PVC (polyvinyl chloride) films.
[0019] As an example, the surface material may be a single-layer sheet or a laminate of two or more layers of sheets.
[0020] As an example, the thickness of the surface material may be 10 to 1000 μm.
[0021] As an example, the weight per unit area of the surface material may be 120 to 150 g / m².
[0022] Another aspect of the present application provides a method for manufacturing a mineral-based fiber board composite.
[0023] As an example, the present manufacturing method comprises the steps of: preparing a mineral-based fiber core; and manufacturing a composite by placing a surface material containing melamine on both sides of the mineral-based fiber core and then heat-pressing it, wherein the weight per unit area of the melamine contained in the composite is 80 to 110 g / m², and the mineral-based fiber core and the surface material may have an adhesion strength of 0.1 to 100 kgf / cm² as a result of the ASTM D4541 adhesion test.
[0024] As an example, the surface material may include a low pressure melamine sheet.
[0025] As an example, the surface material may additionally include any one of ASA (acrylonitrile styrene acrylate), PP (polypropylene), PET (poly(ethylene terephthalate)), and PVC (polyvinyl chloride) films.
[0026] As an example, heat pressing is 150 to 190 It can be performed within the temperature range.
[0027] As an example, heat pressing can be performed for 25 to 35 seconds.
[0028] As an example, heat pressing can be performed such that mineral fiber core and surface materials are placed inside a press mold to form a composite by heating and pressing, and then demolded from the mold after cooling.
[0029] As an example, a release liner containing a fluorine coating layer may be inserted into each of the upper and lower parts of the press mold. Effects of the invention
[0031] According to one embodiment of the present application, a mineral-based fiber board composite with improved strength can be provided.
[0032] According to one embodiment of the present application, a mineral-based fiber board composite having a low shrinkage rate can be provided.
[0033] According to one embodiment of the present application, a mineral-based fiber board composite having a low coefficient of thermal expansion can be provided.
[0034] According to one embodiment of the present application, a mineral-based fiber board composite having excellent adhesion to LPM can be provided.
[0035] According to one embodiment of the present application, a method for manufacturing a mineral-based fiber board composite with a low defect rate can be provided.
[0036] According to one embodiment of the present application, a mineral-based fiber board composite that can be used as an insulating material, an exterior material, or an interior material can be provided. Brief explanation of the drawing
[0038] FIG. 1 is a schematic cross-sectional view of a mineral-based fiber board composite according to one aspect of the present application. FIG. 2 is a schematic cross-sectional view of a mineral fiber board composite according to another aspect of the present application. FIG. 3 is a flowchart for explaining a method for manufacturing a mineral-based fiber board composite according to one aspect of the present application. FIG. 4 is an image illustrating a heat pressing process among the methods for manufacturing a mineral-based fiber board composite according to one aspect of the present application. FIGS. 5 to 7 are images illustrating an experiment to measure the adhesion of a mineral-based fiber board composite according to one aspect of the present application. Specific details for implementing the invention
[0039] The terms used in this application are used merely to describe specific embodiments and are not intended to limit the invention. The singular expression includes the plural expression unless the context clearly indicates otherwise. In this application, terms such as "comprising" or "having" are intended to indicate the presence of features, components, etc. described in the specification, and do not imply that one or more other features or components, etc., are not present or cannot be added.
[0040] Unless otherwise defined, all terms used herein, including technical or scientific terms, have the same meaning as generally understood by those skilled in the art to which the present invention pertains. Terms such as those defined in commonly used dictionaries should be interpreted as having a meaning consistent with their meaning in the context of the relevant technology, and should not be interpreted in an ideal or overly formal sense unless explicitly defined in this application.
[0041] Hereinafter, the mineral-based fiber board composite of the present application and the method for manufacturing the same will be described in detail with reference to the attached drawings. However, the attached drawings are exemplary, and the scope of the mineral-based fiber board composite of the present application and the method for manufacturing the same is not limited by the attached drawings.
[0042] Hereinafter, a mineral-based fiber board composite, which is one aspect of the present application, will be described.
[0043] FIG. 1 is a schematic cross-sectional view of a mineral-based fiber board composite according to one aspect of the present application.
[0044] As illustrated in FIG. 1, the mineral fiber board composite (1) includes a surface material (20), a mineral fiber core material (10), and a surface material (20).
[0045] The mineral fiber core material (10) may be a mineral fiber board, and a mineral fiber board is a general term for building materials made by melting minerals, such as basalt or granite, at a high temperature. The mineral fiber board uses mineral fibers as aggregates, and in order to secure strength and bonding power, a resin (especially phenolic resin) is mixed in and processed into a board shape by heat compression. In addition, these can be used as insulation and exterior materials, and especially as interior materials due to their low tVOC non-combustibility.
[0046] Here, the mineral is preferably a natural mineral and may contain a rich amount of metal. Generally, igneous rocks contain a rich amount of metal. Basalt and granite are typical examples. In addition, to reduce costs, it may include sludge generated after iron ore smelting.
[0047] Among these, basalt fiber is an inorganic fiber produced by melt-spinning basalt through 200 to 500 nozzles at a temperature of about 1400°C, and is a high-performance fiber similar to glass fiber. The basalt fiber is characterized by excellent tensile strength and modulus of elasticity, as well as superior chemical resistance, and above all, a very wide working temperature range of -260 to 560°C. In addition, it has the advantages of being lightweight (7 kg / m² based on 6T), making it easy for workers to install, having a low water absorption rate, and excellent processability.
[0048] As mentioned above, due to the characteristics of aggregates composed of mineral fibers, they lack hardness and there is a possibility of dust being generated during processing; therefore, in this application, a surface material is applied as described below.
[0049] The weight per unit area of the surface material (20) may be 120 to 150 g / m². As described below, the weight of the surface material may be composed of melamine and other pulps. As the weight of the surface material increases, the melamine content also increases. When the surface material is 120 g / m² or more, the melamine content is higher than that of conventional general LPM, so the amount of melamine absorbed by the substrate increases, and as a result, the surface area that can be bonded is expanded, thereby resolving poor adhesion and surface defects.
[0050] The surface material (20) contains melamine, and the weight per unit area of the melamine contained in the composite may be 80 to 110 g / m². The range of melamine may include melamine that has penetrated from the surface material into the mineral fiber core. Specifically, when the weight per unit area of the surface material is 120 to 150 g / m², the weight per unit area of the melamine contained in the composite may be calculated to be 80 to 110 g / m². This is because the surface material is composed of melamine and other pulp, etc., so the surface material and the mineral fiber core are attached to each other by heat pressing, and in a composite in which a certain amount of melamine contained in the surface material has penetrated into the mineral fiber core, the weight per unit area of the melamine contained in the composite may be calculated to be 80 to 110 g / m² excluding other components. At this time, when the melamine content is in the range of 80 to 110, the amount of melamine absorbed into the core material is appropriate, and as a result, the surface area where the mineral fiber core material and melamine can bond is increased, thereby resolving poor adhesion and surface defects.
[0051] Melamine may be included as a low pressure melamine sheet.
[0052] Low-pressure melamine sheets (LPM sheets) can be attached to both sides of a mineral fiber board. Low-pressure melamine sheets can be attached to the mineral fiber board by high-temperature heat pressing without the use of separate adhesives.
[0053] Low-pressure melamine sheets offer the advantages of low cost, easy processability, high surface properties, and diverse design possibilities. The resin requires a core material known as decorative paper, which can be formed by repeatedly impregnating and drying materials such as urea resin and melamine resin.
[0054] MDF or PB is mainly used as the core material, and due to the characteristics of LPM that require thermoforming, the relatively high compression strain of wood-based MDF or PB allows the resin portion of the low-pressure melamine sheet to penetrate deep into the core material, thereby providing high adhesion strength, while also distributing the force evenly across the pressure-receiving surface, resulting in uniform and excellent surface properties.
[0055] Low-pressure melamine sheets can create three-dimensional shapes by using various mirror plates such as glossy, matte, embossed, or logos on the surface when heat-pressed, and can produce a natural tactile feel in terms of color or texture, giving the user a friendly feeling.
[0056] Additionally, the surface material (20) may further include any one of ASA (acrylonitrile styrene acrylate), PP (polypropylene), PET (poly(ethylene terephthalate)), and PVC (polyvinyl chloride) films.
[0057] The surface material may be a single-layer sheet. However, the surface material may be a laminate of two or more layers of sheets. FIG. 2 is a schematic cross-sectional view of a mineral-based fiber board composite according to another aspect of the present application.
[0058] Mineral fiber core material has a low thermal deformation rate (10) such as mineral fiber board. -5Materials are limited to those with a compressive strength of 1% or less (100% or less) and compressive strength of 50 MPa or less. Additionally, if the surface porosity is 1% or less, the bonding area is narrow during LPM hot pressing, and the amount of resin impregnated / absorbed into the material is small, making it difficult to secure the required physical properties. These limitations can be overcome by designing the surface material with two or more layers.
[0059] As shown in FIG. 2, the surface material can be laminated in two layers.
[0060] Generally, when laminated in two layers, structural stability can be improved compared to when laminated in one layer. When laminated in one layer, simply increasing the impregnation amount increases only the amount of hard plastic, and does not increase the amount of fibers that affect structural stability. In addition, when using thick fibers, the impregnation time is long and there may be a limit where the resin remains on the fiber surface, so the aforementioned advantages can be provided when laminated in two layers.
[0061] In other words, when laminated in two or more layers, the hard resin remains between the soft fiber layers, resulting in structural stability and reduced exposure of the resin to the outside, which can lead to superior wear resistance. Additionally, since the impregnation time is not increased by intentionally using thick fiber layers, it is advantageous in terms of process time.
[0062] The thickness of the surface material can be 10 to 1000 μm.
[0063] For example, in the case of a single layer, it may be 15 to 300 μm, and in the case of a two-layer layer, it may be 50 to 1000 μm.
[0064] Here, the mineral fiber core and surface layer have an adhesion of 0.1 to 100 kgf / ㎠ as a result of the ASTM D4541 adhesion test.
[0065] The adhesion evaluation method uses the Bond adhesion test method with a two-component epoxy adhesive according to KS M ISO 4624. For example, after fixing the sample with an epoxy bond, the opposite surface of the sample is fixed to a measuring jig using another epoxy bond, and then an attractive force is applied in a vertical direction to measure the pressure at which the bonding surface to be measured is destroyed or detached.
[0066] Here, the composite can have a hardness of 4B to 3H in a pencil hardness test.
[0067] Pencil hardness test? You can follow ISO 15184, and after fixing the pencil and sample at a 45-degree angle, apply a vertical force of 7.5 N to evaluate whether the sample is damaged.
[0068] These mineral-based fiber board composites exhibit improved strength, low shrinkage, and low thermal expansion, making them suitable for use as insulation, exterior, and interior materials.
[0070] Hereinafter, a method for manufacturing a mineral-based fiber board composite, which is one aspect of the present application, will be described.
[0071] FIG. 3 is a flowchart for explaining a method for manufacturing a mineral-based fiber board composite according to one aspect of the present application.
[0072] As illustrated in FIG. 3, a method for manufacturing a mineral-based fiber board composite according to one aspect of the present application may include the step of preparing a mineral-based fiber core material (S10); and the step of manufacturing a composite by placing a surface material containing 120 g / m² or more of melamine on both sides of the mineral-based fiber core material and then heat-pressing it (S20).
[0073] Hereinafter, a method for manufacturing a mineral-based fiber board composite, which is one aspect of the present application, will be described step by step.
[0074] First, a mineral fiber core is prepared (S10).
[0075] Mineral fiber cores include mineral fiber boards, which are a general term for building materials made by melting minerals, such as basalt or granite, at high temperatures. Mineral fiber boards use mineral fibers as aggregates and can be processed into board form by mixing in a resin (especially phenolic resin) and heat-compressing it to ensure strength and bonding. Additionally, they can be used as thermal insulation and exterior materials, and particularly as interior materials due to their low tVOC non-combustibility.
[0076] Here, the mineral is preferably a natural mineral and may contain a rich amount of metal. Generally, igneous rocks contain a rich amount of metal. Basalt and granite are typical examples. In addition, to reduce costs, it may include sludge generated after iron ore smelting.
[0077] Among these, basalt fiber is an inorganic fiber made by melt-spinning basalt through 200 to 500 nozzles at a temperature of about 1400°C, and is a high-performance fiber similar to glass fiber.
[0078] The above basalt fiber is characterized by excellent tensile strength and elastic modulus, excellent chemical resistance, and above all, a very wide working temperature range of -260 to 560℃.
[0079] In addition, it has the advantages of being lightweight (7 kg / m² based on 6T), easy for workers to install, low water absorption, and excellent processability.
[0080] As mentioned above, due to the characteristics of aggregates composed of mineral fibers, they lack hardness and there is a possibility of dust being generated during processing; therefore, in this application, a surface material is applied as described below.
[0081] Then, a composite is manufactured by placing a surface material containing melamine on both sides of the mineral fiber core material and then heat-pressing it (S20).
[0082] Surface materials can be applied to both sides of the above mineral-based fiber core material.
[0083] The surface material may include a low pressure melamine sheet.
[0084] Low-pressure melamine sheets can be attached to both sides of a mineral fiber board by heat pressing. Low-pressure melamine sheets can be attached to a mineral fiber board by high-temperature heat pressing without the use of separate adhesives.
[0085] Low-pressure melamine sheets offer the advantages of low cost, easy processability, high surface properties, and diverse design possibilities. Low-pressure melamine sheet resins require a core material known as decorative paper, which can be formed by repeatedly impregnating and drying materials such as urea resin and melamine resin.
[0086] MDF or PB is mainly used as a mineral fiber core material. Due to the characteristics of low-pressure melamine sheets requiring thermoforming, the relatively high compression strain of wood-based MDF or PB allows the resin portion of the low-pressure melamine sheet to penetrate deep into the core material, thereby providing high adhesion strength, while also distributing the force evenly across the pressure-receiving surface, resulting in uniform and excellent surface properties.
[0087] Low-pressure melamine sheets can create three-dimensional shapes by using various mirror plates such as glossy, matte, embossed, or logos on the surface when heat-pressed, and can produce a natural tactile feel in terms of color or texture, giving the user a friendly feeling.
[0088] In addition, it is desirable to apply the surface material at a weight of 120 g / m² or more. Generally, low-pressure melamine sheets are used at a weight of approximately 72 to 80 g / m²; however, in this case, complete curing does not occur, and whitening occurs, resulting in poor surface roughness. To improve these problems, the present application has optimized the weight of the surface material and limited its use to 120 g / m² or more. However, in addition to these weight conditions, the heat pressing conditions have been optimized as described below.
[0089] In addition, the surface material may further include any one of ASA (acrylonitrile styrene acrylate), PP (polypropylene), PET (poly(ethylene terephthalate)), and PVC (polyvinyl chloride) films.
[0090] FIG. 4 is an image illustrating a heat pressing process among the methods for manufacturing a mineral-based fiber board composite according to one aspect of the present application.
[0091] Thermal pressing can be performed such that mineral fiber core and surface materials are placed inside a press mold, a composite is formed by heating and pressing, and the composite is demolded from the mold after cooling.
[0092] As an example, a release liner containing a fluorine coating layer may be inserted into each of the upper and lower parts of the press mold.
[0093] Release properties can be improved by including a release liner. The release liner is not specifically limited, but any release liner can be applied as long as it includes a fluorine coating layer.
[0094] Specifically, heat pressing can be performed in a temperature range of 150 to 190 ℃. The lower limit of the temperature range may be 150 ℃, 155 ℃, 160 ℃, or 165 ℃. On the other hand, the upper limit of the temperature range may be 190 ℃, 185 ℃, 180 ℃, or 175 ℃.
[0095] If the heat pressing temperature is less than 150°C, the degree of incomplete curing is high, so sufficient physical properties such as poor adhesion, poor strength and hardness, and whitening may not be secured. On the other hand, if the heat pressing temperature exceeds 190°C, the resin may carbonize or oxidize in the air, causing discoloration or the formation of bubbles.
[0096] Specifically, heat pressing can be performed within a time range of 25 to 35 seconds. The lower limit of the time range may be 25 seconds, 26 seconds, 27 seconds, or 28 seconds. On the other hand, the upper limit of the time range may be 35, 34 seconds, 33 seconds, or 32 seconds.
[0097] If the heat pressing time is less than 25 seconds, the degree of incomplete curing is high, so sufficient physical properties such as poor adhesion, poor strength and hardness, and whitening may not be secured. On the other hand, if the heat pressing time exceeds 35 seconds, the resin may carbonize or oxidize in the air, causing discoloration or the formation of bubbles.
[0098] The present application may optionally use a metal mirror surface during press compression, and the metal mirror surface may be included for the durability of the press.
[0099] At this time, the temperature condition range and time condition range of the heat pressing can be limited to a more desirable range depending on the difference of each component.
[0100] In one example, the mineral fiber core and surface layer have an adhesion of 0.1 to 100 kgf / ㎠ as a result of the ASTM D4541 adhesion test. As described above, the adhesion evaluation method uses the Bond adhesion test method with a two-component epoxy adhesive according to KS M ISO 4624. For example, after fixing the sample with an epoxy bond, the sample is fixed to a measuring jig using another epoxy bond on the opposite surface of the sample, and then an attractive force is applied in a vertical direction to measure the pressure at which the adhesive surface to be measured is destroyed or detached.
[0101] In one example, the surface roughness value of the composite produced by the above-described method may be 2 to 4. If complete curing does not occur and whitening occurs, the surface roughness value increases, which allows for the inference of the defect rate. A mineral-based fiber board produced by the manufacturing method according to the present application can secure a surface roughness value of 2 to 4.
[0103] The present application will be explained in more detail below through experimental examples. Here, a low-pressure melamine sheet was used, but this is merely one example of a surface material, and the present application is not limited thereto, and other surface materials may be used.
[0105] [Experimental Example 1]
[0106] The surface roughness value according to the weight of the LPM material was measured, and an experiment to measure the defect rate was performed as follows.
[0107] [Example 1]
[0108] After preparing the press, fluorine-coated release paper was inserted into the upper and lower parts of the press.
[0109] In a press, from the bottom to the top, a metal mirror surface (flat form without embossing), LPM, mineral fiber core material, LPM, and a metal mirror surface were laminated in sequence. However, the LPM was laminated at 120 g / m² (weight per unit area of the surface material).
[0110] A composite containing LPM, a mineral fiber core, and LPM was manufactured by heat-pressing the laminate at 170°C for 30 seconds at a pressure of 200 kgf / ㎠.
[0111] Afterward, the sample of Example 1 was prepared by cooling and demolding.
[0112] [Comparative Example 1]
[0113] After preparing the press, fluorine-coated release paper was inserted into the upper and lower parts of the press.
[0114] Inside the press, from the bottom to the top, a metal mirror surface (flat form without embossing), LPM, core material, LPM, and a metal mirror surface were laminated in that order. However, the LPM was laminated at 70 g / m².
[0115] A composite containing LPM, a mineral fiber core, and LPM was manufactured by heat-pressing the laminate at 170°C for 30 seconds at a pressure of 200 kgf / ㎠.
[0116] Afterward, the sample of Comparative Example 1 was prepared by cooling and demolding.
[0117] [Comparative Example 2]
[0118] After preparing the press, fluorine-coated release paper was inserted into the upper and lower parts of the press.
[0119] Inside the press, from the bottom to the top, a metal mirror surface (flat form without embossing), LPM, core material, LPM, and a metal mirror surface were laminated in sequence. However, the LPM was laminated at 80 g / m².
[0120] A composite containing LPM, a mineral fiber core, and LPM was manufactured by heat-pressing the laminate at 170°C for 30 seconds at a pressure of 200 kgf / ㎠.
[0121] Afterward, the sample of Comparative Example 2 was prepared by cooling and demolding.
[0122] [Evaluation 1]
[0123] Surface roughness values were measured for each of the samples in Example 1, Comparative Example 1, and Comparative Example 2.
[0124] FIG. 7 is an image illustrating an experiment to measure the surface roughness of a mineral-based fiber board composite according to one aspect of the present application.
[0125] The surface roughness values measured three times for each sample are shown in Table 1 below.
[0126] Unit (㎛) 1st 2nd 3rd average Example 1 2.241 2.029 2.305 2.192 Comparative Example 1 4.706 4.882 4.107 4.565 Comparative Example 2 4.498 3.979 4.542 4.440
[0127] As shown in Table 1, it was confirmed that the surface roughness value of Example 1 was significantly lower compared to the surface roughness values of Comparative Example 1 and Comparative Example 2. Through this, it was confirmed that when the weight of LPM intended in this application is included, complete curing occurs, no whitening phenomenon is observed, and the defect rate is minimized.
[0128] [Evaluation 2]
[0129] Cross-edge adhesion was measured for each of the samples of Example 1, Comparative Example 1, and Comparative Example 2. Specifically, a cross-edge pill test was performed.
[0130] Refer to ASTM D 3359 or ISO 2409, and make a judgment by measuring the area separated / detached from the grid area. If 0%, it was judged as 5B, the best, and if 65% or more, it was judged as 0B, the worst.
[0131] For each sample, the results before and after taping were measured and are shown in Table 2 below.
[0132] Images of the taping before and after for Example 1, Comparative Example 1, and Comparative Example 2 are shown in FIGS. 5 to 7, respectively.
[0133] Before taping After taping Example 1 100 100 Comparative Example 1 76 6 Comparative Example 2 94 27
[0134] As shown in Table 2, it was confirmed that the peel test value of Example 1 was significantly higher compared to the peel test values of Comparative Example 1 and Comparative Example 2. Specifically, Example 1 is 5B because the difference before and after taping is 0%. On the surface, Comparative Example 1 is 0B because the difference before and after taping is 70%. In addition, Comparative Example 2 is 0B because the difference before and after taping is 69%.
[0135] [Experimental Example 2]
[0136] For Example 1 and Comparative Example 1 and Comparative Example 2, the pencil hardness of each sample was measured according to the method specified in KS M ISO 15184 through the experimental method as described below.
[0137] The hardness measurement method is as follows. First, a mechanical pencil sharpener was used to sharpen the wooden portion of the pencil lead while maintaining its cylindrical shape. Then, the pencil was placed vertically on abrasive paper and rubbed back and forth to straighten the tip of the lead, and the test specimen was placed on a level and fixed to a horizontal plane. The tip of the pencil was placed on the test specimen and pushed in a specific direction while applying a load of 7.5 N from vertically upward. After the test was completed, it was visually inspected. The above process was performed sequentially from 8B to 9H, and the stage at which damage was detected was defined as the pencil hardness of the corresponding test specimen. The measured values are shown in Table 3 below.
[0138] Pencil hardness Example 1 4H Comparative Example 1 2H Comparative Example 2 1H
[0139] As shown in Table 3, it can be seen that the pencil hardness value of Example 1 is superior to the pencil hardness values of Comparative Example 1 and Comparative Example 2.
[0140] [Experimental Example 3]
[0141] For Example 1 and Comparative Example 1 and Comparative Example 2, the adhesion of each sample was measured through the experimental method as follows.
[0142] The adhesion measurement method is the Pull-off test specified in ASTM D4541. Specifically, after fixing the test specimen to the floor, the surface material applied to the specimen was fixed vertically to a dolly using a two-component epoxy adhesive, and the specimen was left for 24 hours to cure. After attaching the testing machine to the dolly and aligning it with the specimen, the force applied to the surface was increased at a rate of 20 kgf / min to induce fracture. Adhesion was calculated by determining the force and area at fracture, and the measured values are shown in Table 4 below.
[0143] Adhesion strength (kgf / cm²) 2 ) Example 1 Unmeasurable (Core material damaged) Comparative Example 1 231.84 Comparative Example 2 169.11
[0144] As shown in Table 4, the adhesion strength of Example 1 could not be accurately measured due to damage to the core material, while Comparative Examples 1 and 2 were measured as above. Therefore, it can be inferred that the adhesion strength is greater than or equal to the tensile strength of the core material, and it can be confirmed that it has been improved. Although the above description refers to the preferred embodiments of the present application, those skilled in the art will understand that the present application can be modified and changed in various ways without departing from the spirit and scope of the invention as described in the following claims. Explanation of the symbols
[0145] 1: Fiberboard composite 10: Mineral fiber core 20: Surface material
Claims
Claim 1 A mineral fiber board composite comprising a surface material; a mineral fiber core material; and the surface material sequentially, wherein the surface material comprises a low pressure melamine sheet, the weight per unit area of the surface material is 120 to 150 g / m², the weight per unit area of the melamine included in the composite is 80 to 110 g / m², and the adhesion strength between the mineral fiber core material and the surface material is 0.1 to 100 kgf / cm² as a result of the ASTM D4541 adhesion test. Claim 2 In claim 1, the composite is a mineral-based fiber board composite having a hardness of 4B to 4H in the ISO 15184 pencil hardness test. Claim 3 delete Claim 4 In claim 1, the surface material is a mineral-based fiber board composite further comprising any one of ASA (acrylonitrile styrene acrylate), PP (polypropylene), PET (poly(ethylene terephthalate)), and PVC (polyvinyl chloride) films. Claim 5 In claim 1, the surface material is a mineral-based fiber board composite that is a single-layer sheet or a laminate of two or more layers of sheets. Claim 6 A mineral-based fiber board composite according to claim 1, wherein the thickness of the surface material is 10 to 1000 μm. Claim 7 delete Claim 8 A method for manufacturing a mineral fiber board composite according to claim 1, comprising the steps of: preparing a mineral fiber core material; and manufacturing a composite by placing a surface material containing melamine on both sides of the mineral fiber core material and then heat-pressing, wherein the weight per unit area of the melamine contained in the composite is 80 to 110 g / m², and the mineral fiber core material and the surface material have an adhesion strength of 0.1 to 100 kgf / cm² as a result of an ASTM D4541 adhesion test. Claim 9 delete Claim 10 A method for manufacturing a mineral-based fiber board composite according to claim 8, wherein the surface material further comprises any one of ASA (acrylonitrile styrene acrylate), PP (polypropylene), PET (poly(ethylene terephthalate)), and PVC (polyvinyl chloride) films. Claim 11 A method for manufacturing a mineral-based fiber board composite according to claim 8, wherein the heat pressing is performed in a temperature range of 150 to 190 ℃. Claim 12 A method for manufacturing a mineral-based fiber board composite according to claim 8, wherein heat pressing is performed for 25 to 35 seconds. Claim 13 A method for manufacturing a mineral fiber board composite according to claim 8, wherein heat pressing is performed such that a mineral fiber core material and a surface material are placed in a press mold to form a composite by heating and pressing, and then demolded from the mold after cooling. Claim 14 A method for manufacturing a mineral-based fiber board composite according to claim 13, wherein a release paper containing a fluorine coating layer is inserted into each of the upper and lower parts of a press mold.
Citation Information
Patent Citations
Fiber-reinforced decorative laminate
EP1600288A1
Incombustible decorative plate
JP1998076598A
Interior board
KR1020200047425A